Pengembangan Media Card Match Cicle untuk Meningkatkan Motivasi Belajar Pada Pembelajaran IPS Siswa Kelas IV SDN 01 Kandri - Muthi’a, Farihatul; Sari, Elok Fariha (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research aims to develop learning media Card Match Circle which is valid and effective in social studies learning in class IV SDN 01 Kandri to increase student learning motivation. Based on the results of observations made, it was found that the lack of motivation to learn in class IV students was due to the limited use of learning media in social studies learning. The research uses development with the ADDIE development model (Analysis, Design, Development, Implementation dan Evaluation). The data sources in this research were 28 students. Media development Card Match Circle is in the very feasible category with media validation results obtained at 91% and material validation obtained at 85%. The results of product effectiveness are obtained from pretest and posttest with a result of 0.674 which is in the quite effective category. Thus, it can be concluded that learning media Card Match Circle in social studies learning in class IV was declared valid and effective enough to be used in increasing students' learning motivation at SDN 01 Kandri.